Pharmacophore studies of 1, 3, 4-oxadiazole nucleus: Lead compounds as α-glucosidase inhibitors. (August 2019) - Khan, Haroon; Zafar, Muhammad; Patel, Seema; Shah, SM Mukarrum; Bishayee, Anupam
Abstract: α-glucosidase inhibition is a rational approach in the effective management of type 2 diabetes. Several inhibitors of this enzyme class are in clinical use, but are riddled with efficacy, potency and safety challenges. For this reason, new effective α-glucosidase inhibitors are under investigation. Compounds with 1, 3, 4-oxadiazole nucleus have shown preclinical efficacy as α-glucosidase inhibitors and as anti-inflammatory agents. Moreover, 1, 3, 4-oxadiazoles also play important role in pesticide chemistry, polymer science, and they are considered as the building blocks in the production of new molecular agents for bioactive molecules. In the present study, computational analyses were carried out for various 1, 3, 4-oxadiazole (which were divided into BF2 & BF3 series); the most active compound was taken as a potent inhibitor, and pharmacophore were formed from that compound, followed by validation against a test database. The pharmacophore-based virtual screening was performed and, by successive eliminations, six compounds of different interactions with the significant amino acid residues were selected as the lead compounds. It is concluded that these six compounds with 1, 3, 4-oxadiazoles nucleus might be used as promising drug candidates in α-glucosidase inactivation and thus we recommend further in vitro and in vivo pharmacological and safety studies.